Elaboración De Una Tisana A Partir De Hojas De Aguacate (Persea Americana Mill), Orégano (Origanum Vulgare L.) Y Fibra De Coco - HannÃbal, Brito; Paúl, Palmay; Ãngel, Silva; Edmundo, Caluña; Iván, Ramos; Margoth, Mariño; Eliana, Romero; Luis, Guadalupe; Valeria, RodrÃguez (European Scientific Journal, ESJ, 2016)
A tisane was made from the leaves of avocado, oregano and coconut fiber; with the purpose of establishing a process for obtaining this product. This research begins with the identification of the species of the vegetal elements and their respective active principles. The production process was developed at the laboratory level, it involved a set of stages of transformation of the raw material to reach the final product, considering specific variables or parameters such as: PH, temperature, average diameter in mass, moisture of the vegetal elements and time required in certain stages. In addition, the control of conservation of active principles were carried out by comparing spectra of reception samples in grinding and subsequent sieving. The formulation of the tisane was established by considering the content of active ingredients of therapeutic interest and conducting tastings with the respective surveys, establishing the following composition per gram of tisane: 50% oregano leaves, 40% coconut fiber and 10% avocado leaves; with an acceptability of the product of 65.12% by the consumers of both genders. At the end of the investigation, it was determined that the preparation process for the tisane includes the following steps: reception, selection, cleaning / washing, disinfection, pre-drying, dehydration, manual cutting, Prepackaging, sterilization, formulation, labeled and packaging.